2014
DOI: 10.1093/eurheartj/ehu017
|View full text |Cite
|
Sign up to set email alerts
|

Optimal rhythm-control strategy for recurrent atrial tachycardia after catheter ablation of persistent atrial fibrillation: a randomized clinical trial

Abstract: This study demonstrates superiority of CA over AAD for recurrent AT after persistent AF ablation with regard to SR maintenance, long-term safety and QoL improvement. However, CA use might be limited by a higher risk for periprocedural complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…However, all these factors can not be effectively resolved by short-term use of AADs. A recent report by Zhang et al[ 48 ] has shown that a second ablation procedure was more effective in maintaining sinus rhythm than AADs in patients with late atrial arrhythmia recurrence after catheter ablation of AF. As we above discussed, the main causes for early recurrence of atrial arrhythmias included post-ablation inflammations, temporary autonomic imbalance, and also the delay of atrial radiofrequency lesion formation[ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, all these factors can not be effectively resolved by short-term use of AADs. A recent report by Zhang et al[ 48 ] has shown that a second ablation procedure was more effective in maintaining sinus rhythm than AADs in patients with late atrial arrhythmia recurrence after catheter ablation of AF. As we above discussed, the main causes for early recurrence of atrial arrhythmias included post-ablation inflammations, temporary autonomic imbalance, and also the delay of atrial radiofrequency lesion formation[ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whether to perform additional ablation including tricuspid valve isthmus ablation, continuous fractionated atrial electrogram ablation, and LA linear ablation was decided by the operator and/or the attending physician. The ablation procedure followed the method described by Liu X et al [16, 17]. …”
Section: Methodsmentioning
confidence: 99%
“…Various approaches have been used to treat patients with AF [3]. However, clinical trials have shown unsatisfactory outcomes with existing therapeutic strategies [4].…”
Section: Introductionmentioning
confidence: 99%